Strawberry Intake Ameliorates Oxidative Stress and Decreases GABA Levels Induced by High-Fat Diet in Frontal Cortex of Rats - Sandoval-Salazar, Cuauhtémoc (Antioxidants (Basel), 2019)
It has been proposed that there is a correlation between high-fat diet (HFD), oxidative stress and decreased γ-aminobutyric acid (GABA) levels, but this has not been thoroughly demonstrated. In the present study, we determined the effects of strawberry extract intake on the oxidative stress and GABA levels in the frontal cortex (FC) of obese rats. We observed that an HFD increased lipid and protein oxidation, and decreased GABA levels. Moreover, UV-irradiated strawberry extract (UViSE) decreased lipid peroxidation but not protein oxidation, whereas non-irradiated strawberry extract (NSE) reduced protein oxidation but not lipid peroxidation. Interestingly, NSE increased GABA concentration, whereas UViSE was not as effective. In conclusion, our results suggest that an HFD increases oxidative damage in the FC, whereas strawberry extract intake may ameliorate the disturbances associated with HFD-induced oxidative damage.